Dampak Kebijakan Dana Desa terhadap Peningkatan Kesejahteraan Masyarakat (Studi Komparasi di Desa Ponggok, Desa Tegalrejo, dan Desa Kalangan, Klaten, Jawa Tengah) - Fadli Razzak; Zuly Qodir (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2020)
A fundamental change in the government system in Indonesia after the reforms is the implementation of decentralization and real regional autonomy. Giving village funds is a form of fulfilling the village's rights for the implementation of its own autonomy to grow and develop following diversity, participation, autonomy, empowerment, democratization of the community and increasing the role of the village government in order to provide services and improve the welfare of the community in areas that are adrift . Therefore, this study aims to reveal the impact of village fund policies on improving people's welfare and reducing unemployment in Ponggok Village, Tegalrejo Village, and Kalangan Klaten Village. Ponggok village was chosen because it is a pilot village that has managed to manage village funds provided for the welfare of its people. Ponggok Village uses its village funds to provide infrastructure to support the sustainability of Ponggok Tourism Village, conduct training programs, toilets for each house, as well as other assistance that can improve the welfare of its citizens, and the entire community participates in the programs. As a result, the program can significantly reduce unemployment. Tegalrejo Village uses its village funds to improve village infrastructure and train its community. Desa Kalangan uses its village funds to improve village infrastructure, reforestation, training and community development. However, the results of the management of the village fund of the two villages have not been able to improve the economy and reducing unemployment, due to the lack of community participation in the programs being implemented.Â Keywords: regional autonomy, village funds, community welfare, unemployment